Production of human embryonic kidney 293T cells stably expressing C-X-C chemokine receptor type 4 (CXCR4) as a screening tool for anticancer lead compound targeting CXCR4 - Dinh Thi Thai Ha (2022)
Aim: The C-X-C chemokine-receptor type 4 (CXCR4) is an emerging target for cancer drug discovery due to its high expression in cancer cells. The present study aimed to produce CXCR4 overexpressing HEK293T cells for a non-radioactive binding assay as a platform to identify drug candidates targeting CXCR4. Main methods: HEK293T cells stably expressing human CXCR4 were constructed by transfection of CXCR4 plasmids from the human CXCR4 gene. The CXCR4 overexpressing HEK293T cells were obtained by fluorescence-activated sorting and verified by conducting the competition binding assay of a known CXCR4 inhibitor, AMD3100 (plerixafor), to determine the IC50 value against monoclonal anti-human CD184 (hCD184) antibody tagged with fluorescence probe, phycoerythrin (PE). The non-radioactive binding assay using CXCR4 overexpressing HEK293T cells and PE-anti hCD184 was applied as a platform for identifying the target of natural compounds that exhibited cytotoxicity against cancer cell lines. Key findings: The CXCR4 overexpressing HEK293T cells were produced with high expression (99.8%). The IC50 value of plerixafor determined by fluorescence tagged antibody-based competition assay using our developed cells agree with previously reported values using a radioligand binding assay. We observed no significant displacement of bound PE-anti-hCD184 by the test natural compounds which could be due to non-specific binding to other functional targets or organelles, low potency of the natural compounds, or binding to CXCR4 at deeper pockets. Significance: The verified non-radioactive binding assay can serve as an alternative screening tool for anticancer lead compounds targeting CXCR4 and an essential tool for proof of mechanism study in the drug discovery.